The Gambia hepatitis intervention study (GHIS) - Hainaut, Pierre (Iatreia, 2007)
The Gambia Hepatitis Intervention Study (GHIS) is a collaborative undertaking by the International Agency for Research on Cancer, The Government of the Republic of The Gambia and the Medical Research Council of the United Kingdom. This programme was launched in 1986 with the objective of evaluating the efficacy of Hepatitis B (HB) vaccination in childhood in the prevention of HB infection, chronic liver disease and primary liver cancer in a population at high risk. The implementation of this trial involves three overlapping phases: Phase l (1986-1990): V Vaccination accination of appro approximately ximately 60,000 children. HB vaccine, which was approved by the World Health Organisation, was integrated into the Gambian Expanded Programme of Immunisation (EPI) in a phased manner over a four-year period from July 1986 to February 1990. During this period, two groups of children were recruited, one comprising about 60,000 children who received all vaccines in the EPI schedule plus the HB vaccine, the other comprising a similar number of children who received all vaccines except HB. Since February 1990, HB vaccination is offered to all newborns as part of the EPI schedule in The Gambia. Phase ll (1991-1997): Estimate of efficacy of HB vac- vaccine cine against infection and chronic carriage. Longitudinal and cross-sectional surveys were carried out in selected groups of vaccinated (Group 1) and unvaccinated (Group 2). These two subsets have provided evidence of the short-term efficacy of HB vaccine in preventing infection and chronic carriage. By the end of the first decade of life, the vaccine prevents 84% and 94% of HBV infections and chronic carriage, respectively, despite waning antibody levels during the period. Phase lll (since 1998): Long-term follow-up through Cancer Registration. The aim of this phase is to carry out a surveillance of the population of The Gambia, to identify cases of chronic liver disease (cirrhosis) and liver cancer. A linkage is made between the records of cases occurring in subjects within the age-range of the GHIS cohort, and the GHIS database of vaccinated children, to determine whether the individual belongs to the vaccinated or unvaccinated cohort. The components of Phase III are: 1. Detection and ascertainment of cancer cases and cases of chronic liver disease in the population of The Gambia, through support to liver cancer diagnosis in the public and private health sector, and support to Laboratory and Histopathology Services. 2. Registration of cancer cases and of cases of chronic liver disease through the National Cancer Registry (NCR), a population-based cancer registry established in 1986. 3. Record linkage of identified cases with the GHIS database of vaccinated/non-vaccinated children, so that the net effect of HB vaccination in preventing liver cancer can ultimately be assessed. In parallel with the development of the three phases above, the GHIS framework has fostered studies on viral, environmental and genetic factors in hepatocellular carcinoma, biomarkers of HB Infection and aflatoxin exposure, long term efficacy of HB vaccination and monitoring of breakthrough injections.